Placental pathology in different degrees of pregnancy induced hypertension - S., Rajyalakshmi; BS, Vani; Bai P., Jijiya (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Pregnancy induced hypertension (PIH), a well-known medical complication of pregnancy is potentially morbid for the foeto-maternal health. It is also responsible for perinatal morbidity and mortality due to its effects on the growing foetus. Objectives: The present study was undertaken to analyse the histomorphological and gross features of placenta in pregnancy induced hypertension in relation to severity of hypertension, age of the patient, parity and gestational age. Materials and Methods: The current study was done at Gandhi Hospital, Secunderabad, India on antenatal cases of PIH of varying degrees. The placentas of these patients following delivery were studied and statistic significance between different histologic findings and severity of PIH calculated. Results: Incidence of PIH was highest in women above 26yrs of age (42%) and was found to be almost equal in both multiparous (52%) and primiparous (48%) women. Foetal outcome was worst in severe PIH (IUGR of 28.8% and IUD of 17.85%). The gross abnormalities noted, retroplacental hematomas (42%) and small sized placentae (24%) were more often seen in severe PIH. The consistent histological changes observed include fibrinoid necrosis (86%), thickened basement membrane (74%), increased syncitial knots (72%), stromal fibrosis (54%), cytotrophoblastic proliferation (46%), intervillous haemorrhage (40%), and calcification (34%). Conclusion: The pathological changes in the placenta seen in PIH patients are almost equally prevalent irrespective of the parity. Cases with severe PIH displayed features of placental underperfusion more frequently than with mild to moderate PIH. Hence watchful individualized management of PIH helps reduce the incidence of complications and morbidity.